Correlation between Salivary Cortisol Levels in Patients with Psychological Stress and Incidence of Recurrent Aphthous Stomatitis: A Scoping Review - Fiki Muhammad Ridho; Aufa Alma’as Nabila Maulidina; Bella Pardian Nur Allifiah (Indonesian Journal of Dentistry, 2024)
Background: The etiology of recurrent aphthous stomatitis (RAS) is still unclear, but psychological stress is thought to contribute to the occurrence of RAS. One of the biomarkers for evaluating psychological stress levels is through measuring salivary cortisol levels. This scoping review aims to review and evaluate the correlation between salivary cortisol levels in individuals with psychological stress and an increased incidence of RAS.Methods: A scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines through databases on PubMed, ScienceDirect, Scopus, ProQuest, and Google Scholar until November 2023. All included studies discussed salivary cortisol levels in RAS patients and controls.Results: Eleven of the twelve studies showed an increase in salivary cortisol levels in RAS patients compared with the control group, with eight of them having a statistically significant increase. In addition, eight studies evaluated the level of psychological stress in respondents, seven of which concluded that there was an increase in stress levels in RAS patients with five of them showing a statistically significant increase.Conclusion: In conclusion, the present study concludes that there is a correlation between increased salivary cortisol levels in individuals with psychological stress and an increased incidence of RAS.